Analysis of the Impact of the Open Unemployment Rate and Household Consumption on Poverty in Sumatra from 2021 to 2025 - Tri Febriani Sipayung; Trivena Kezia Silaban; Apriani Hutabarat; Aryani Sairun (International Journal For Advanced Research, 2026)
Poverty remains a major development challenge in Indonesia, particularly on the island of Sumatra, which has a diverse economic landscape. This study aims to examine the impact of the Open Unemployment Rate (OUR) and Household Consumption on poverty rates across ten provinces in Sumatra during the period 2021–2025. By applying multiple linear regression to panel data, it was found that both independent variables simultaneously and significantly influence poverty (F = 8.850; p = 0.001). Individually, household consumption exhibits a strong negative effect on poverty at a significance level of 0.000, indicating that an increase in household spending correlates with a decrease in the number of people living in poverty. Meanwhile, the open unemployment rate has a positive effect at a 10% significance level (p = 0.055), meaning that a rise in unemployment tends to drive an increase in poverty. The regression model used explains 27.4% of the variation in poverty, whilst the remainder is influenced by other factors outside the model. These findings underscore the importance of policies that promote job creation and strengthen household purchasing power within poverty alleviation strategies in the Sumatra region.